Dilemma of Legal Transplantation in CCS Regulations: Between Harmonization and Adaptation to Local Context - Wahyu Fahmi Rizaldy; Elbouche Chems Sadjda Lilleh (University of Jember, Indonesia, 2024)
Climate change necessitates innovative solutions like Carbon Capture and Storage (CCS) to reduce CO2 emissions. CCS involves capturing and storing CO2 in underground geological formations. Implementing CCS in Indonesia requires a comprehensive regulatory framework addressing technical standards, permits, monitoring, and financing, while also considering environmental and social risks. This research analyzes the dilemma of